Method for measuring component content of perfluoroelectrolyte for aluminum electrolytic refining
By using an XRF spectrometer to prepare and analyze the melting method in the perfluoroelectrolyte for aluminum electrolytic refining, the calibration curve was established, and the problem of difficulty in quickly and accurately determining the content of perfluoroelectrolyte in the prior art was solved, and fast and accurate detection results were achieved.
Patent Information
- Application Number
- CN202411744817.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
AI Technical Summary
It is difficult to quickly and accurately determine the various components of perfluorolytes for aluminum electrolytic refining in the prior art, and the traditional methods have problems such as incomplete digestion, long digestion time, complex detection steps and poor aging.
By adding high-purity barium fluoride, calcium fluoride, sodium fluoride, lithium fluoride and aluminum fluoride to the flux and dropping into the ammonium iodide solution, a series of standard samples were prepared, and samples were prepared and analyzed by using an XRF spectrometer were used to prepare and analyze the melting method to establish a calibration curve to achieve rapid and accurate determination of the samples to be tested.
The rapid and accurate detection of the content of perfluorolyte components for aluminum electrolytic refining is achieved, the sample processing steps are simplified, the detection time is shortened, and the accuracy and reproducibility of the detection results are improved.
Smart Images

Figure CN119555719A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for determining the content of perfluorinated electrolyte components for aluminum electrolytic refining, and belongs to the field of aluminum electrolytic refining. Background Art
[0002] Three-layer liquid aluminum electrolytic refining is an important production method for producing 99.99% refined aluminum. The middle layer in the electrolytic cell is composed of molten salt electrolyte, and its density is generally 2.6-2.8g / cm 3 . The intermediate layer molten salt electrolyte usually adopts a perfluorinated system composed of fluoride, aluminum fluoride, sodium fluoride, calcium fluoride and lithium fluoride. The perfluorinated system electrolyte has the advantages of low water absorption, low degree of hydrolysis and low volatility. However, in actual industrial production, perfluorinated electrolytes will inevitably volatilize, resulting in fluctuations in the composition of the electrolyte, affecting the efficient operation of electrolysis and increasing energy consumption. Therefore, it is necessary to analyze and monitor the electrolyte composition in real time before the tank, and correct the composition when necessary to ensure efficient and stable electrolytic refining.
[0003] At present, there are many methods for detecting various elements in perfluorinated electrolytes used for aluminum electrolytic refining. For example, the analysis and detection methods for fluorine element include distillation-thorium nitrate titration volumetric method, fluoride ion selective electrode method and ion chromatography; barium and calcium elements use ICP analysis method; sodium element can be analyzed by atomic absorption spectroscopy; aluminum element is EDTA volumetric method.
[0004] The above traditional methods have the problem of incomplete digestion of electrolytes for perfluorinated electrolytes, so it is difficult to accurately measure. Even if a method that can completely digest is developed, there are still problems such as long digestion time and more reagents. At the same time, multiple types of instruments are required to measure the elements of the electrolyte. It is impossible to use a single instrument and method for determination, which will inevitably lead to complicated detection steps, poor timeliness, and inability to perform pre-tank detection. Therefore, it is necessary to establish a method for rapid analysis of the content of each component in perfluorinated electrolytes.
[0005] X-rays are widely used in the aluminum industry to measure the molecular ratio of bauxite, alumina, aluminum hydroxide, cryolite, aluminum fluoride and aluminum electrolytic electrolyte. However, perfluorinated electrolytes used for aluminum electrolytic refining are very different from them because they contain lithium fluoride, and the content is about 10%, in order to improve the conductivity of the molten salt and reduce the cell pressure. At present, for the detection of perfluorinated electrolytes, because XRF cannot measure the lithium element, technicians generally do not add lithium elements when preparing standard samples, but the inventors of the present invention have found that the measurement is inaccurate without adding lithium fluoride, because the lithium element will significantly affect the X-ray fluorescence intensity of other elements to be measured. If it is not corrected, the barium, calcium, sodium and aluminum content will not be accurately measured. Therefore, it is necessary to prepare a set of standard samples of perfluorinated electrolytes for aluminum electrolytic refining, and accurately measure the element content of the electrolyte through a calibration method, and obtain the content of each component through calculation.
[0006] The purpose of the present invention is to establish a method for determining the content of perfluorinated electrolyte components for aluminum electrolytic refining, in order to solve the problem that the content of perfluorinated electrolyte components cannot be determined quickly in one time. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for determining the content of perfluoroelectrolyte components for aluminum electrolytic refining, which can solve the problem of being unable to quickly determine the contents of multiple components of perfluoroelectrolyte at one time, and at the same time has the advantages of accurate and rapid detection results.
[0008] In order to achieve the above object, the technical solution of the present invention is to provide a method for determining the content of perfluorinated electrolyte components for aluminum electrolytic refining, comprising the following steps:
[0009] (1) adding high purity barium fluoride, calcium fluoride, sodium fluoride, lithium fluoride and aluminum fluoride into flux, and dropping ammonium iodide solution;
[0010] (2) Prepare a series of standard samples covering the range of perfluorinated electrolyte elements for aluminum electrolytic refining;
[0011] (3) Standard samples were prepared by the fusion method, and calibration curves for calcium, aluminum, sodium, and barium were prepared using an XRF spectrometer;
[0012] (4) The perfluorinated electrolyte for aluminum electrolytic refining to be tested is prepared by the fusion plate method in the same way as the standard sample, and the sample to be tested is analyzed by XRF spectrometer to determine the content of each element therein, and the content of each component in the sample to be tested is calculated.
[0013] Furthermore, the purity of the aluminum fluoride, sodium fluoride, calcium fluoride, barium fluoride and lithium fluoride used to prepare the standard sample in step (1) is ≥99.9%.
[0014] Furthermore, in step (1), the flux is a mixture of Li2B4O7 and LiBO2, and the mass percentage of the two is between 1:1 and 3:1; the percentage of the total mass of high-purity barium fluoride, calcium fluoride, sodium fluoride, lithium fluoride and aluminum fluoride to the mass of the flux is between 1:20 and 1:5.
[0015] Preferably, the flux in step (1) is a mixture of Li2B4O7 and LiBO2, and the mass percentage of the two is between 1.5:1 and 2:1.
[0016] Furthermore, the concentration of the ammonium iodide solution in step (1) is 100-300 g / L.
[0017] Preferably, the concentration of the ammonium iodide solution in step (1) is 200-300 g / L, the dripping amount is 1-5 mL, and the further dripping amount is preferably 1-2 mL.
[0018] Furthermore, the content (wt.%) of each element in the standard sample prepared in step (2) is in the range of 5%-25% for barium, 5%-20% for aluminum, 5%-20% for sodium, and 3%-15% for calcium.
[0019] Preferably, the content (wt.%) of each element in the standard sample prepared in step (2) is in the range of 9.39%-23.49% for barium, 6.02%-16.43% for sodium, 8.36%-16.07% for aluminum, and 3.08%-12.31% for calcium. The content (wt.%) of each element in the standard sample prepared in step (2) should be the same as the content of each element in the aluminum electrolytic refining perfluorinated electrolyte to be tested, or cover the content of each element in the aluminum electrolytic refining perfluorinated electrolyte to be tested.
[0020] Furthermore, in step (2), the number of standard samples with different element contents is ≥5.
[0021] Furthermore, in step (3), the sample preparation by the fusion plate method is to place the standard sample into a fusion sample machine, and the heating temperature is 800-1000° C. and the heating time is 5-15 minutes.
[0022] Preferably, in step (3), the heating temperature is 900° C. and the heating time is 10 min.
[0023] Further, the R of the calibration curve of each element in the perfluorinated electrolyte in step (3) 2 ≥0.99.
[0024] Furthermore, in step (4), the measured content (wt.%) of the elements in the sample to be tested is in the range of 5%-25% for barium, 5%-20% for aluminum, 5%-20% for sodium, and 3%-15% for calcium.
[0025] Furthermore, in step (3), when the content of any element in the standard sample differs from the content of any element measured by the X-ray fluorescence spectrometer by ≥0.5wt.%, recalibration or formulation of a calibration curve is required.
[0026] Beneficial Effects
[0027] (1) Standard samples. At present, the country and the aluminum industry do not have standard samples of perfluorinated electrolytes in aluminum electrolytic refining. Therefore, the present invention creates an XRF standard sample method and standard sample based on this system, and the obtained standard curve regression coefficient is good (R 2 ≥0.99), which provides a basis for detecting the content of perfluorinated electrolyte components used in aluminum electrolytic refining.
[0028] (2) Pre-tank detection. The chemical analysis method requires the sample to be tested to be digested, and the digestion process takes more than three hours, or even longer. At the same time, there is an incomplete digestion phenomenon, which affects the accuracy of the result. The method of the present invention only needs to add the sample to be tested to the flux and the release agent (ammonium iodide), and make a glass sheet in the melting machine, which only takes more than 10 minutes, and the XRF spectrometer analyzes the sample in about 5 minutes. Therefore, compared with other more complicated chemical analysis methods, the detection time can be greatly shortened. It only takes 15 minutes to obtain the detection result of the perfluorinated electrolyte component content, which can realize the rapid analysis of the electrolyte component content before adding the material, and accurately control the amount of material added.
[0029] (3) Simple operation. The glass slides made of standard samples can be preserved for a long time, and the samples to be tested do not need complicated pre-treatment such as digestion process. The sample processing steps are simplified, the operation difficulty is reduced, and the workload of the test personnel is reduced.
[0030] (4) Accurate data. When the perfluorinated electrolyte for aluminum electrolytic refining is pressed into a tablet, the particle size effect and mineral effect of the powder cannot be avoided, which will affect the accuracy of the results. The fused sheet method can completely eliminate the particle size effect and mineral effect, reduce the error of sample preparation, and obtain highly accurate test results.
[0031] (5) Good data reproducibility. This method can obtain high-precision test results. The same sample can be measured multiple times with small differences in the results, and the RSD% is less than 0.3%. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is the calibration curve of each element in Example 1.
[0033] Figure 2 Comparison of X-ray fluorescence intensity between the standard sample and the sample to be tested in Comparative Example 1.
[0034] Figure 3 The X-ray fluorescence intensity change of the element to be measured when 1% lithium fluoride is added in Comparative Example 3.
[0035] Figure 4 The X-ray fluorescence intensity comparison between the standard sample of the present invention and the sample to be tested in Comparative Example 3 is shown in FIG. DETAILED DESCRIPTION
[0036] The specific implementation modes of the present invention are further described in detail below in conjunction with the embodiments.
[0037] Example 1: A method for determining the content of perfluorinated electrolyte components for aluminum electrolytic refining
[0038] (1) Add barium fluoride, calcium fluoride, sodium fluoride, lithium fluoride and aluminum fluoride into a flux (the mass percentage of Li2B4O7 to LiBO2 is 67:33), wherein the purity of aluminum fluoride, sodium fluoride, barium fluoride, calcium fluoride and lithium fluoride is 99.99%, and the mass percentage of the five to the flux is 1:5, and then drop ammonium iodide solution (1 mL) is added, and the solution concentration is 300 g / L.
[0039] (2) Five series of standard samples covering the range of element contents of perfluorinated electrolytes for aluminum electrolytic refining were prepared. The content (wt.%) of each element in the standard samples ranged from 9.39% to 21.92% for barium, 6.02% to 15.33% for sodium, 9.00% to 16.07% for aluminum, and 4.62% to 12.31% for calcium. The content of each element in the five standard samples is shown in Table 1.
[0040] Table 1 Content of each element in standard samples
[0041]
[0042] (3) Place the standard sample in a melting machine, set the heating temperature to 900°C, and the heating time to 10 min. Shake the crucible during heating to prepare a glass sheet.
[0043] (4) The prepared standard sample glass pieces were used to make calibration curves for aluminum, sodium, barium, and calcium on an X-ray fluorescence spectrometer. 2 They are 0.9998, 0.9980, 0.9994, and 0.9997 respectively. The results are as follows Figure 1 shown.
[0044] (5) The perfluoroelectrolyte for aluminum electrolytic refining to be tested is prepared into a sample glass sheet by adopting the same steps (1) (3) as those for preparing the standard sample glass sheet, ensuring the same sample preparation conditions as the standard sample glass sheet, and then measured by X-ray fluorescence spectrometer to obtain the content of each element, and calculate the content of each component in the perfluoroelectrolyte for aluminum electrolytic refining to be tested.
[0045] The content of each component can be calculated based on the element content (Table 2).
[0046] Table 2 XRF analysis composition determination results
[0047]
[0048] It can be seen from Table 2 that the relative errors of the measured values of the perfluorinated electrolyte components for aluminum electrolytic refining to be measured and the standard values are both less than 1%, and the accuracy is relatively high.
[0049] The same sample was tested multiple times, and the precision analysis results are shown in Table 3. The standard deviation (SD) of the content of each component in the perfluoroelectrolyte is ≤0.04, and the relative standard deviation (RSD) is ≤0.23%, with high precision.
[0050] Table 3 Component precision test results
[0051]
[0052] Example 2: A method for determining the content of perfluorinated electrolyte components for aluminum electrolytic refining
[0053] (1) Add barium fluoride, calcium fluoride, sodium fluoride, lithium fluoride and aluminum fluoride into a flux (the mass percentage of Li2B4O7 to LiBO2 is 60:40), wherein the purity of aluminum fluoride, sodium fluoride, barium fluoride, calcium fluoride and lithium fluoride is 99.99%, and the mass percentage of the five to the flux is 1:20, and then drop ammonium iodide solution (2 mL) is added, and the solution concentration is 200 g / L.
[0054] (2) A series of 7 standard samples covering the range of element contents of perfluorinated electrolytes for aluminum electrolytic refining were prepared. The content (wt.%) of each element in the standard samples ranged from 12.53% to 23.49% for barium, 3.08% to 11.28% for calcium, 8.76% to 16.43% for sodium, and 8.36% to 13.50% for aluminum. The content of each element in the 7 standard samples is shown in Table 4 below.
[0055] Table 4 Content of each element in standard samples
[0056]
[0057] (3) Place the standard sample in a melting machine, set the heating temperature to 900°C, and the heating time to 10 min. Shake the crucible during heating to prepare a glass sheet.
[0058] (4) The prepared standard sample glass pieces were used to make calibration curves for aluminum, sodium, barium, and calcium on an X-ray fluorescence spectrometer. 2 They are 0.9997, 0.9991, 0.9997 and 0.9995 respectively.
[0059] (5) The perfluoroelectrolyte for aluminum electrolytic refining to be tested is prepared into a sample glass sheet by adopting the same steps (1) (3) as those for preparing the standard sample glass sheet, ensuring the same sample preparation conditions as the standard sample glass sheet, and then measured by X-ray fluorescence spectrometer to obtain the content of each element, and calculate the content of each component in the perfluoroelectrolyte for aluminum electrolytic refining to be tested.
[0060] The content of each component can be calculated based on the element content (Table 5).
[0061] Table 5 XRF analysis results of components
[0062]
[0063] It can be seen from Table 5 that the relative errors of the measured values of the perfluorinated electrolyte components for aluminum electrolytic refining and the standard values are all ≤0.21%, and the accuracy is relatively high.
[0064] The same sample was tested several times, and the results of precision analysis are shown in Table 6. The SD of the content of each component in the perfluorinated electrolyte was ≤ 0.04, and the RSD was ≤ 0.19%, with high precision.
[0065] Table 6 Component precision test results
[0066]
[0067] Comparative Example 1
[0068] (1) Mix high-purity reagents of barium fluoride, calcium fluoride, sodium fluoride, lithium fluoride and aluminum fluoride to prepare a series of 5 standard samples covering the content range of perfluorinated electrolyte elements for aluminum electrolytic refining, wherein the purity of aluminum fluoride, sodium fluoride, barium fluoride, lithium fluoride and calcium fluoride is 99.99%. The content (wt.%) of each element in the standard samples ranges from 9.39% to 21.92% for barium, 6.02% to 15.33% for sodium, 9% to 16.07% for aluminum, and 4.62% to 12.31% for calcium. The content of each element in the 5 standard samples is shown in Table 1.
[0069] (2) The standard sample is ground and sieved to make the particle size of the powder sample reach 200 mesh.
[0070] (3) Boric acid edging-backing tableting was used, the tablet press pressure was 35t, and the holding time was 30s.
[0071] (4) The prepared standard sample is pressed into a tablet and the calibration curves of aluminum, sodium, barium and calcium are prepared on an X-ray fluorescence spectrometer.
[0072] (5) The perfluoroelectrolyte for aluminum electrolytic refining to be tested is ground and pressed into a pellet in the same manner as the steps (2) and (3) for preparing the standard sample pellet, ensuring that the same sample preparation conditions as the standard sample are used, and then measured using an X-ray fluorescence spectrometer to obtain the content of each element, and the content of each component in the perfluoroelectrolyte for aluminum electrolytic refining to be tested is calculated.
[0073] The standard sample is made of high-purity reagent powders of barium fluoride, calcium fluoride, sodium fluoride, lithium fluoride and aluminum fluoride, which are mixed and ground into tablets. The standard sample prepared by this method has a large mineral effect with the perfluorinated electrolyte to be tested, resulting in a large difference in the X-ray fluorescence intensity of each element, making it impossible to obtain accurate element content. When the element content of the standard sample is the same as that of the sample to be tested, the XRF fluorescence intensity result is as follows: Figure 2 As shown, the detection requirements of the samples to be tested cannot be met.
[0074] Comparative Example 2
[0075] The chemical digestion for determining the elements barium, aluminum, calcium and sodium in the perfluorinated electrolyte is as follows: put the sample in a platinum crucible, add a small amount of water and 4 mL of perchloric acid, heat the platinum crucible on a heating table, heat at low temperature until the white smoke is gone, add 5 mL of hydrochloric acid (the volume ratio of hydrochloric acid to water is 1:1) and 30 mL of deionized water after cooling, then put it on the heating table, heat at low temperature until the solution is clear, filter and dilute to a volumetric flask. Then ICP can be used for measurement. It takes 4-5 hours to digest the sample in this process, and it may not be completely digested.
[0076] This method only requires adding high-purity barium fluoride, calcium fluoride, sodium fluoride, lithium fluoride and aluminum fluoride to the flux, and dripping the ammonium iodide solution; the sample is prepared by the melting plate method to prepare a glass plate. The operation is simple, the required time is greatly reduced, and the pre-tank detection can be realized. At the same time, the results are similar to those obtained by chemical digestion, as shown in Table 7.
[0077] Table 7 Comparison of XRF and ICP values
[0078]
[0079] Comparative Example 3
[0080] (1) Add barium fluoride, calcium fluoride, sodium fluoride and aluminum fluoride into a flux (the mass percentage of Li2B4O7 to LiBO2 is 67:33), wherein the purity of aluminum fluoride, sodium fluoride, barium fluoride and calcium fluoride is 99.99%, and the mass percentage of the four to the flux is 1:5, and then drop ammonium iodide solution (1 mL) is added, and the solution concentration is 300 g / L.
[0081] (2) The sample of step (1) is placed in a melting machine, the heating temperature is set to 900° C., the heating time is 10 min, and the crucible is shaken during heating to prepare a glass sheet.
[0082] (3) Take the barium fluoride, calcium fluoride, sodium fluoride and aluminum fluoride samples prepared in step (1), add 1% lithium fluoride by weight of the total sample, and prepare glass sheets in the manner of steps (1) and (2).
[0083] The X-ray fluorescence intensity of barium, sodium, calcium and aluminum in the above two samples was measured. The results are as follows: Figure 3 As shown. It can be seen that a small amount of lithium fluoride can affect the X-ray fluorescence intensity of barium, sodium, calcium, and aluminum, so the influence of lithium fluoride cannot be ignored. The present invention adds lithium fluoride to the standard sample, which can reduce the influence of lithium element on the element to be measured, thereby achieving accurate measurement of the element to be measured. When the lithium fluoride content of the standard sample and the sample to be measured is similar, the X-ray fluorescence intensity results of each element are as follows Figure 4 As shown, the X-ray fluorescence intensities of the elements barium, sodium, aluminum and calcium to be measured are basically the same, which can meet the requirements of accurate measurement.
Claims
1. A method for determining the content of perfluorinated electrolyte components for aluminum electrolytic refining, characterized in that: The steps include: (1) adding high purity barium fluoride, calcium fluoride, sodium fluoride, lithium fluoride and aluminum fluoride into flux, and dropping ammonium iodide solution; (2) Prepare a series of standard samples covering the range of perfluorinated electrolyte elements for aluminum electrolytic refining; (3) Standard samples were prepared by the fusion method, and calibration curves for calcium, aluminum, sodium, and barium were prepared using an XRF spectrometer; (4) The perfluorinated electrolyte for aluminum electrolytic refining to be tested is prepared by the fusion plate method in the same way as the standard sample, and the sample to be tested is analyzed by XRF spectrometer to determine the content of each element therein, and the content of each component in the sample to be tested is calculated.
2. The method according to claim 1, characterized in that The purity of the aluminum fluoride, sodium fluoride, calcium fluoride, barium fluoride and lithium fluoride used to prepare the standard sample in step (1) is ≥99.9%.
3. The method according to claim 1, characterized in that In the step (1), the flux is a mixture of Li2B4O7 and LiBO2, and the mass percentage of the two is between 1:1 and 3:1; the total mass percentage of high-purity barium fluoride, calcium fluoride, sodium fluoride, lithium fluoride and aluminum fluoride to the mass of the flux is between 1:20 and 1:
5.
4. The method according to claim 1, characterized in that: The concentration of the ammonium iodide solution in step (1) is 100-300 g / L.
5. The method according to claim 1, characterized in that The content (wt.%) of each element in the standard sample prepared in step (2) is in the range of 5%-25% for barium, 5%-20% for aluminum, 5%-20% for sodium, and 3%-15% for calcium.
6. The method according to claim 1, characterized in that In the step (2), the number of standard samples with different element contents is ≥5.
7. The method according to claim 1, characterized in that In the step (3), the sample preparation by the fusion plate method is to place the standard sample into a fusion sample machine, and the heating temperature is 800-1000° C. and the heating time is 5-15 minutes.
8. The method according to claim 1, characterized in that The R of the calibration curve of each element in the perfluorinated electrolyte in step (3) 2 ≥0.
99.
9. The method according to claim 1, characterized in that: In the step (4), the measured content (wt.%) of the elements in the sample to be tested is in the range of 5%-25% for barium, 5%-20% for aluminum, 5%-20% for sodium, and 3%-15% for calcium.
10. The method according to claim 1, characterized in that In the step (3), when the content of any element in the standard sample differs from the content of the element measured by the X-ray fluorescence spectrometer by ≥0.5wt.%, recalibration or formulation of a calibration curve is required.
Citation Information
Patent Citations
Method for determining element of aluminum fluoride using X ray fluorescence spectrophotometry
CN101059456A
Sodium fluoride sintering method for determinating molecular ratio of aluminium electrolyte
CN1100807A
X-ray flourescent quickly analysing method of fine aluminium electrolytic component
CN1869670A
Analysing method of excess alumina content in aluminium electrolyte
CN1912611A